2012
DOI: 10.2147/ijn.s28745
|View full text |Cite
|
Sign up to set email alerts
|

Poloxamer 407/TPGS mixed micelles for delivery of gambogic acid to breast and multidrug-resistant cancer

Abstract: Background: Delivery of a high concentration of anticancer drugs specifically to cancer cells remains the biggest challenge for the treatment of multidrug-resistant cancer. Poloxamers and D-α-Tocopheryl polyethylene glycol 1000 succinate (TPGS) are known inhibitors of P-glycoprotein (P-gp). Mixed micelles prepared from Poloxamer 407 and TPGS may increase the therapeutic efficacy of the drug by delivering high concentrations inside the cells and inhibiting P-gp. Gambogic acid (GA) is a naturally derived novel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 39 publications
6
29
0
Order By: Relevance
“…Hence, difference in the cytotoxicity between free GA and GAL was found to be negligible in vitro . In similar observations with our study, Saxena and Hussain, (2012) demonstrated that GA encapsulated in poloxamer 407/TPGS showed comparable in vitro cytotoxicity than free GA in breast cancer MCF-7 cells (Saxena and Hussain, 2012). …”
Section: Discussionsupporting
confidence: 89%
“…Hence, difference in the cytotoxicity between free GA and GAL was found to be negligible in vitro . In similar observations with our study, Saxena and Hussain, (2012) demonstrated that GA encapsulated in poloxamer 407/TPGS showed comparable in vitro cytotoxicity than free GA in breast cancer MCF-7 cells (Saxena and Hussain, 2012). …”
Section: Discussionsupporting
confidence: 89%
“…Because it is a small hydrophobic molecule, iodine was incorporated into the hydrophobic cores of the micelles. This caused a conversion of I 3 − to I 2 , which maintained the saturated concentration of I 2 solution [ 29 ]. The CMC value of each group was determined by plotting the absorption intensity against the logarithm of the polymer mass concentration ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The critical micelle concentrations (CMC) of PEG-PLA, VE-TPGS, and their mixture (VE-TPGS/PEG-PLA = 13/87, w/w) were determined using iodine UV spectroscopy as described previously [ 29 ]. A set of polymer solutions at various concentrations (1 ml, 0.0001% to 0.1%, w/v) was prepared with 5 μl of KI/I 2 standard solution added.…”
Section: Methodsmentioning
confidence: 99%
“…Zhu et al also reported the dual functionality of TPGS in poly(lactic-co-glycolic acid) (PLGA) nanoparticles as a pore-forming agent and stabilizer that resulted in small particle size, high encapsulation efficiency and fast release of docetaxel and P-gp inhibition to overcome MDR in vivo [34] (Scheme 4A). Increasing number of similar formulations have incorporated TPGS to deliver anti-cancer drugs in multidrug resistant cancers [3541]. Similar concept of pharmacologically active polymer surfactant using embelin, a known inhibitor of X-linked inhibitor of apoptosis protein, was recently advanced by the Li lab [42,43].…”
Section: Polymeric Drugs In Cancer Treatmentmentioning
confidence: 99%